Influence of the margin vegetation on the conservation of aphid biological control in apple orchards - Santos, Luan Alberto Odorizzi [UNESP]; Botelho Costa, Marlice; Lavigne, Claire; Fernandes, Odair Aparecido [UNESP]; Bischoff, Armin; Franck, Pierre (Springer Nature, 2018)
The influence of three margin strip treatments (wildflower strips, grass strips and spontaneous vegetation) adjacent to apple orchards on the biological control of Dysaphis plantaginea Passerini (Hemiptera: Aphididae) was compared during two consecutive years. The wildflower strips provided the highest amount of floral resources. Within the margin strips, hoverflies responded positively to higher resource provisioning whereas ladybird abundance did not differ between strip treatments. Within the orchards, the presence of parasitoids, hoverflies, and ladybirds in aphid colonies and the predation of sentinel aphids were not significantly affected by the adjacent strip treatments. The number of natural enemies observed in aphid colonies was mainly driven by aphid number. Aphid numbers were higher close to the margin strips suggesting that aphid colonization from orchard edges may counteract the positive effect of wildflower strips on natural enemy abundance and on a reduction of aphid infestation. The results confirm the positive influence of floral resource provisioning by wildflower strips on the conservation of aphid natural enemies, but also suggest that effects of wildflower strips on aphid regulation inside orchards are not very strong compared with spontaneous vegetation naturally occurring in the margins.
Keywords: Aphididae; Aphidophagous predators; Apple orchard; Conservation biological control; Dysaphis plantaginea; Floral resources; Hemiptera